CAREvolution for Generation Z: Integrating Penyang Hinje Simpei Values into Educational Psychology Interventions Based on Subjective Well-Being as a Determinant of Resilience - Raisa Vienlentia; Linda; Miko (Universitas Pendidikan Ganesha, 2025)
Generation Z demonstrates learning characteristics that are highly adaptive to technological developments. However, the increasing academic demands pose new challenges in strengthening students’ psychological resilience. This condition underscores the importance of internal protective factors that enable students to adapt effectively and recover from various academic pressures. This study aims to analyze and examine the contribution of subjective well-being to academic resilience among Generation Z students. A quantitative approach with a survey design was employed. The participants consisted of 225 students selected using a saturated sampling technique. Data were collected using the Indonesian Academic Resilience Scale (IARS) and the Subjective Well-Being Scale (SWBS), both of which have demonstrated validity and reliability. Data were analyzed using linear regression to test the relationships between variables. The results indicate that subjective well-being has a positive and significant effect on academic resilience. Components such as life satisfaction, positive affect, and the ability to manage negative affect were found to contribute to enhancing students’ adaptive capacity in facing academic challenges. This study concludes that subjective well-being is a significant determinant of academic resilience. The findings provide implications for the development of educational psychology interventions that strengthen cognitive, emotional, and contextual value-based aspects to sustainably support students’ psychological resilience.